Immaturity of Oculomotor Capabilities During a Reading Task in Children Born Prematurely: An Eye Tracker Study. Issue 3 (June 2022) - Bucci, Maria Pia; Caldani, Simona; Boutillier, Béatrice; Frérot, Alice; Farnoux, Caroline; Virlouvet, Anne-Laure; Rideau-Batista-Novais, Aline; Trousson, Clémence; Biran, Valerie
To our knowledge, there are no studies recording the reading eye movements of children born prematurely. We examined the oculomotor patterns during reading of 23 children born prematurely ( M age = 7.8, SD = 0.2 years) to compare them with those from two groups of children born at full-term who were matched for chronological age or reading age, respectively. We found the oculomotor reading pattern in children who were preterm to be similar to that of children who were full-term and matched for reading age; this shared pattern was characterized by longer duration of fixations, frequent prosaccades of smaller amplitude and several backward saccades. In contrast, when these two groups were compared to full-term children matched for chronological age, the latter group showed significantly shorter duration of fixations, less frequent saccades and larger amplitude prosaccades. Thus, the oculomotor pattern we observed in 7-year-old children who were either preterm or reading-delayed, relative to their age-matched peers, reflected delayed development of brain areas involved in reading-related eye movements.